Minimally-invasive lateral thoracic and lumbar interbody fusion (LLIF) with expandable interbody cages – Considerations, complications & outcomes - Martin N. Stienen; Gregor Fischer; Linda Bättig; Anand Veeravagu; Benjamin Martens (Brain and Spine)
Introduction: Reports about lateral lumbar or thoracic interbody fusion (LLIF) using expandable interbody spacers are sparse. Research question: To report our experience with the use of expandable spacers for LLIF. Material and methods: We reviewed all consecutive LLIF patients with use of an expandable titanium interbody implant (ELSA® Expandable Integrated LLIF Spacer, Globus Medical Inc, PA (USA)) between September 2018 and January 2024. Results: We identified 503 patients, in which we performed LLIF at 732 levels. In 63 patients (12.5%) and 70 levels (9.6%) an expandable spacer was used. The mean age was 61.4 years, 57.1% were females. LLIF was performed between T11/12 – L4/5 in the setting of fusion procedures (mono-/bisegmental (20; 28.6%), 3–7 segments (29; 41.4%); >7 segments (21; 30.0%)), of which 21 (33.3%), 20 (31.8%) and 22 (34.9%) were for traumatic, deformity/revision and other diagnoses. Surgery included release of the anterior longitudinal ligament in 30 cases (42.9%). Intraoperative adverse events (AEs) were noted in 2 (3.2%), postoperative AEs in 27 (42.9%) at discharge, 17 (27.0%) at 3 months and 14 (22.2%) at 12 months. Segmental sagittal Cobb angle changed from 1.3° (preoperative) to 13.0° at discharge (p < 0.001), 12.7° at 3 months (p < 0.001) and 13.3° at 12 months (p < 0.001). Functional outcome was excellent/good in 43 (68.3%; 5 missing) at 3 months and in 37 (58.7%; 10 missing) at 12 months. Discussion and conclusion: The use of LLIF with an expandable spacer was safe, promoted solid fusion and enabled powerful correction of sagittal segmental Cobb angle, which was maintained during follow-up.